The Argot of Equality: On the Importance of Disentangling “Diversity” and “Remediation” As Justifications for Race-Conscious Government Action - Ronald J. Krotoszynski Jr. (Washington University Law Review, 2010)
The rules governing “benign” forms of race-conscious government action are easy to state but very difficult to apply in practice. A great deal of the difficulty arises from the lack of precision associated with the use of terms of art, such as “diversity,” “remediation,” and “affirmative action.” Each of these terms should have a concrete and separate meaning, but in reality often serve as mere synonyms; this lack of precision in nomenclature is not always accidental. Although broad majorities support efforts to increase “diversity,” race-conscious government action aimed at remediating past racial discrimination enjoys much more limited popular support. The general public's strong antipathy toward remedial race-conscious government action provides a powerful incentive for government officials to mislabel remedial programs as resting on a diversity rationale. Unfortunately, however, mislabeling a remedial affirmative action effort as a non-remedial diversity program can and will lead to virtually automatic judicial invalidation of the program, notwithstanding the fact that a compelling interest in remediation might support the program. The federal courts should consider carefully whether demanding truth in advertising is a higher constitutional value than securing voluntary remedial efforts from local, state, and federal government entities to undo the continuing contemporary effects of past discriminatory behavior. Moreover, the Supreme Court cannot reasonably demand more accuracy from government entities in describing the rationale for race-conscious action than the Court itself observes; the most recent decisions from the Supreme Court, including both Justice O'Connor's majority opinion in Grutter v. Bollinger and Justice Kennedy's critical concurring opinion in Parents Involved in Community Schools v. Seattle School District, both fail to deploy the argot of equality with exacting precision. Race is a difficult topic and plain talk about race is not easy for any government entity — including the federal courts. This state of affairs requires pragmatic realism, rather than empty formalism, in assessing the consistency of benign race-conscious government action with the equal protection mandate. In this regard, permitting government entities to defend benign race-conscious government action as resting on either remedial grounds or a combination of remedial and diversity concerns — regardless of a program's formal “diversity” label — would constitute a modest step in the right direction.
Keywords: Affirmative action programs; Diversity in the workplace; Race preferences (Affirmative action); Judicial process